The Role of Athletic Psychology, Athlete Engagement in Athletic Performance and Athletes Sports Success in China: Does Coaching Behavior Moderates? - Ma GuoJie, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Athletes’ sports success is the driving element for the continued success of the sports centers globally and for this reason, has piqued the interest and attention of contemporary scholars and regulators. Thus, the present study investigates into the impact of athletic psychology and athlete engagement on athletic performance and athletic performance impacts on the athletes’ sports success of the sports center in China. This study also examines the mediating impact of athletic performance among the nexus of athletic psychology, athlete engagement and athletes’ sports success and also explores the moderating role of coaching behavior among the nexus of athletic performance and athletes’ sports success. Questionnaires are used to gather the data, and smart-PLS has been used to test the relations among variables. The results have shown that athletic psychology and athlete engagement have a positive association with athletic performance and athletic performance also has a positive association with athletes’ sports success of the sports centers in China. The results also indicate that athletic performance significantly mediates among the nexus of athletic psychology, athlete engagement and athletes’ sports success while coaching behavior significantly moderates among the nexus of athletic performance and athlete’s sports success.